1993
DOI: 10.1097/00000658-199305010-00014
|View full text |Cite
|
Sign up to set email alerts
|

Management of Major Biliary Complications After Laparoscopic Cholecystectomy

Abstract: Successful management of bile duct injury after laparoscopic cholecystectomy requires careful understanding of the mechanisms, considerable preoperative assessment by experts, and a multidisciplinary approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(104 citation statements)
references
References 4 publications
0
94
0
9
Order By: Relevance
“…It is necessary that the biliary anatomy is defined including all ductal segments as this information is the most important factor in the success of any operative repair (24). The so-called "isolated segments VI and VII" are suspected if these ducts aren't visualized on cholangiography, and then a CT scan or magnetic resonance cholangiography should be performed (19,38). It has been observed that in the majority of the repairs performed without preoperative cholangiography (96%) or with incomplete cholangiography (69%) then success is reduced significantly (24).…”
Section: Injuries Recognized In the Postoperative Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary that the biliary anatomy is defined including all ductal segments as this information is the most important factor in the success of any operative repair (24). The so-called "isolated segments VI and VII" are suspected if these ducts aren't visualized on cholangiography, and then a CT scan or magnetic resonance cholangiography should be performed (19,38). It has been observed that in the majority of the repairs performed without preoperative cholangiography (96%) or with incomplete cholangiography (69%) then success is reduced significantly (24).…”
Section: Injuries Recognized In the Postoperative Periodmentioning
confidence: 99%
“…These injuries lead to high morbidity, mortality, and prolonged hospitalization (18). If major bile duct injury (MBDI) occurs, then it requires a skilled and experienced hepatobiliary surgeon at a tertiary referral center (19). Collaboration with surgeons, interventional radiologists and gastroenterologists is usually necessary for the care of such injuries.…”
Section: Introductionmentioning
confidence: 99%
“…At a later stage of the disease, surgical re-exploration is often difficult because of infection, edema, and scarring in the periportal area [2,4,6]. Furthermore, when the leak involves the intrahepatic ducts, hepatic lobectomy is sometimes required [9].…”
Section: Surgical Interventionmentioning
confidence: 99%
“…The most common mechanism is the so called 'Classic Injury'. This occurs when the operator misidentifies between the cystic duct and the common bile duct during the dissection of Calot's triangle (23,24,25,26). The bile duct is inadvertently transected and common hepatic duct is dissected upwards up to the hilum.…”
Section: Mechanisms Of Bile Duct Injurymentioning
confidence: 99%
“…The routine use of operative cholangiogram as a preventive measure of bile duct injuries (BDI) is controversial (33,34,35,36). However, there is a consenscious that the use of intra operative cholangiogram (IOC) enhances the chance of detection of BDI (18,20,34,37).…”
Section: F Role Of Operative Cholangiogrammentioning
confidence: 99%